Aprendizagens colaborativas na educação profissional e tecnológica: contribuições de um Roteiro Educacional de Compartilhamento do Conhecimento (RECC) - Pizzoni, Magnos Roberto (2024)
This Doctoral thesis in Education at the Federal University of Santa Maria, in Research Line 2, entitled Educational public policies, educational practices and their interfaces, has as Research Theme School Policies and Practices in Professional Education. In this context, this work proposes the elaboration of an educational road map of sharing to be used in Vocational Education schools and research and extension work. For the development of this work, a computer laboratory with Free Software is used as pedagogical resources, which will be available to students throughout the research period, seeking to enable the analysis to verify its effectiveness. In order to achieve the objective proposed in this project, a compilation of some published works was prepared that used Free Software resources in their research that converge with education and promoted actions and studies aimed at sharing knowledge, reinforcing teaching and learning activities. As a methodological resource, action research and systematic literature review were chosen to facilitate reading and understanding of the importance of knowledge sharing. In order to achieve the general objective, it is necessary to develop a pedagogical guide that allows its application in public schools of professional education to strengthen the practice of sharing knowledge and developing critical-reflective thinking. Therefore, it is necessary to carry out specific planned procedures that promote the proof of how the use of Free Software can be used in education, since this category of software is free and it is known to a large part of the academic community that public schools for decades has been suffering from a shortage of financial resources. In this way, this project seeks to reinforce the importance of using this category of software, exposing as an alternative the possibility of building methodological teaching solutions with low investment and that provide a noticeable impact on digital include learning performance.